Oxygen saturation and acute mountain sickness during repeated altitude exposures simulating high-altitude working schedules - Nina F. Waldner; Sara E. Hartmann; Lara Muralt; Mona Lichtblau; Patrick R. Bader; Jean M. Rawling; Ivan Lopez; Silvia Ulrich; Marc J. Poulin; Konrad E. Bloch; Michael Furian (Scientific Reports)
Abstract This study aimed to quantify the effect of two consecutive prolonged, intermittent exposures to high and very high altitudes on oxygen saturation (SpO2) and acute mountain sickness (AMS). For this, healthy lowlanders (N = 21), aged 18–30 years, underwent two 7-day sojourns at the ALMA observatory, Chile (6 h/day at 5050 m, 18 h/day at 2900 m), separated by 1-week at 520 m. SpO2 (pulse oximetry) and AMS severity (AMSc, Environmental Symptom Questionnaire cerebral score) diagnosing AMS (AMSc ≥ 0.7) were assessed daily at both altitudes. The study was registered at www.ClinicalTrials.gov: NCT02730143. SpO2 at 2900 m and 5050 m on arrival was mean ± SD 93.6 ± 0.5% and 79.9 ± 1.0% (P < 0.05 between altitudes), whereas the AMSc scores were 0.43 ± 0.08 and 0.97 ± 0.11 (P < 0.05 between altitudes), respectively. At 2900 m during a 7-day intermittent hypoxic exposure, SpO2 increased by a mean (95% CI) 0.3 %/day (0.1;0.4) and by 0.9 %/day (0.4;1.3) at 5050 m. Similarly, AMSc decreased by 0.05 points/day (0.01;0.08) at 2900 m and by 0.16 points/day (0.11;0.21) at 5050 m. During the second sojourn (vs. 1st sojourn), day 1, SpO2 at 2900 m was unchanged but higher at 5050 m by 2.9% (0.6;5.3). AMSc was lower at 2900 m and 5050 m by 0.37 (0.16;0.59) and 0.37 (0.11;0.63) (P < 0.05 both comparisons vs 1st sojourn), respectively. Acclimatization with the 2nd sojourn increased SpO2 at 2900 m by 0.3%/day (0.1;0.4) and 5050 m by 0.5%/day (0.1;0.8). AMSc remained unchanged with acclimatization at 2900 m but decreased at 5050 m by 0.08 points/day (0.04;0.11). In conclusion, in healthy lowlanders, a 7-day intermittent hypobaric hypoxic exposure improved SpO2 and AMS severity at 2900 m, with larger improvements at 5050 m. During a second identical sojourn, initial AMS severity was reduced despite comparable SpO2 at 2900 m compared to the 1st sojourn. No further acclimatization effects were observed in SpO2 but in AMS symptoms at 2900 m. In contrast, re-exposure to 5050 m showed higher initial SpO2 and lower AMSc values with further improvement with intermittent re-exposures. These findings highlight altitude-dependent acclimatization patterns and confirm pre-conditioning’s effectiveness in preventing AMS.